Effect of slow release fertilizers on growth and fruiting of Khalas date palm - E.H. Salem; H.A.M. Ali (SVU-International Journal of Agricultural Sciences, 2020)
The current investigation was carried out during 2018 and 2019 seasons to study the effect of some fertilizer practices on yield, fruit quality and some mineral content of Khalas date palm grown in a private farm, Luxor Governorate, Egypt. Results showed that significant improved due to use slow release fertilizers as well as comparing total soluble fertilizers in terms of vegetative growth and nutritional status yield, bunch weight and fruit quality during both seasons. Using 600 g of N and 300 g of K via slow release fertilizers form had improved the growth and nutrient status of date palms as well as increase the fertilization efficiency. Also, it could be suggested that fertilizing by 60 to 75 of RDN and RDK via slow release fertilizers to improve the nutrient status of palm and gave the high bunch weight and consequently high yield/palm. Moreover, these fertilization treatments via slow release form gave high yield with good fruit quality compared with using 100% of RDN and RDK via mineral source during both studied seasons. On the light of previous results, it could be concluded that Fertilizing the palm by 60 to 75% of recommended doses of fertilization via slow release form to get high yield with good fruit quality. In addition, reduce the environmental pollution and increase the fertilization efficiency.